2019
DOI: 10.3389/fnmol.2019.00113
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Modeling of Spinal Muscular Atrophy in Drosophila melanogaster

Abstract: Spinal muscular atrophy (SMA) is a neurodegenerative disorder that affects motor neurons, primarily in young children. SMA is caused by mutations in the Survival Motor Neuron 1 (SMN1) gene. SMN functions in the assembly of spliceosomal RNPs and is well conserved in many model systems including mouse, zebrafish, fruit fly, nematode, and fission yeast. Work in Drosophila has focused on the loss of SMN function during larval stages, primarily using null alleles or str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 56 publications
7
57
0
Order By: Relevance
“…Previous studies have shown that loss-of-function mutations in the Drosophila Smn gene result in a variety of phenotypes, including alterations in the sensory-motor neuronal network, abnormal neuromuscular junctions, and defective locomotion [44][45][46][47][48][49]. In addition, we have recently shown that Smn depletion in neurons results in unexpanded wings and unretracted ptilinum [43].…”
Section: Mutations In Dtgs1 Cause Neurological Phenotypesmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that loss-of-function mutations in the Drosophila Smn gene result in a variety of phenotypes, including alterations in the sensory-motor neuronal network, abnormal neuromuscular junctions, and defective locomotion [44][45][46][47][48][49]. In addition, we have recently shown that Smn depletion in neurons results in unexpanded wings and unretracted ptilinum [43].…”
Section: Mutations In Dtgs1 Cause Neurological Phenotypesmentioning
confidence: 94%
“…The unexpanded wing phenotype has been also observed in flies where Smn was specifically silenced in neurons using RNAi [43]. Smn mutant larvae are defective in the sensory-motor neuronal network and exhibit reduced muscle growth and defective locomotion [44,48,49,69]. These phenotypes have been attributed to reduced biogenesis of snRNAs leading to defective splicing of a subset U12 intron-containing RNAs, altering the expression of genes required for motor circuit function such as Stasimon [20].…”
Section: The Functional Relationships Between Tgs1 and Smnmentioning
confidence: 95%
“…In Drosophila SMA models, Smn mutant and RNAi strains have reduced muscle size, motor rhythm, and motor neuron neurotransmission, and result in hindered locomotion 24 , 37 – 41 . Restored expression in the motor circuit of Stasimon , a U12 intron-containing gene, has been reported to correct defects in neuromuscular junction (NMJ) transmission and muscle growth in Drosophila Smn mutants 24 , whereas other studies show that the retention of the Stasimon U12 intron is instead a consequence of the developmental arrest 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that this C-terminal glycine (hsG279) is the least well-conserved position among the three G-motif residues (see Fig. S1A), the spG143V result suggests that the observed metazoan SMA phenotype (human: Type I, [42]; fruitfly: Class 2, [43]) is caused by a distinct mechanism-of-action. Indeed, the C-terminus of the nematode SMN orthologue diverges in this region and a chimeric fusion of the yeast and worm YG boxes fully complements the smn1 null mutation in vivo and displays an oligomerization profile that is very similar to that of the wild-type S.pombe protein in vitro (Fig.…”
Section: Genetic and Biophysical Analysis Of Smn Mutations In Spombementioning
confidence: 99%